2021
DOI: 10.1002/ece3.7957
|View full text |Cite
|
Sign up to set email alerts
|

Drought has negative consequences on aphid fitness and plant vigor: Insights from a meta‐analysis

Abstract: Aphids are abundant in natural and managed vegetation, supporting a diverse community of organisms and causing damage to agricultural crops. Due to a changing climate, periods of drought are anticipated to increase, and the potential consequences of this for aphid–plant interactions are unclear. Using a meta‐analysis and synthesis approach, we aimed to advance understanding of how increased drought incidence will affect this ecologically and economically important insect group and to characterize any potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 84 publications
3
17
2
Order By: Relevance
“…The observation that drought stress had a negative effect on plant physiological processes is in line with previous findings (Ivandic et al, 2000;González et al, 2008;Aslam et al, 2013;Zeppel et al, 2014) and the wider conclusion of meta-analyses (Cornelissen et al, 2008;Leybourne et al, 2021). We identified similar negative effects of drought stress on both plant types: the above-and below-ground dry mass decreased to similar levels when exposed to both drought stress conditions, although, the mass of Hsp5 was lower than Concerto under controlled conditions, indicating that…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The observation that drought stress had a negative effect on plant physiological processes is in line with previous findings (Ivandic et al, 2000;González et al, 2008;Aslam et al, 2013;Zeppel et al, 2014) and the wider conclusion of meta-analyses (Cornelissen et al, 2008;Leybourne et al, 2021). We identified similar negative effects of drought stress on both plant types: the above-and below-ground dry mass decreased to similar levels when exposed to both drought stress conditions, although, the mass of Hsp5 was lower than Concerto under controlled conditions, indicating that…”
Section: Discussionsupporting
confidence: 91%
“…Elevated HvTHIO1 levels in Concerto under the drought stress conditions could contribute towards the observed trend of greater reduction in aphid fitness (compared with Hsp5) under the water stress treatments, or could contribute to the increased expression of aphid detoxification genes when feeding on this plant type. Furthermore, a recent meta-analysis indicated that the defensive processes of plants are generally heightened under drought stress conditions and growth and vigour are reduced, with negative consequences for aphids (Leybourne et al, 2021); the findings of this research are in line with the conclusions drawn from this meta-analysis.…”
Section: Plant Resistance Against Aphids Mediates the Extent To Which...supporting
confidence: 85%
See 2 more Smart Citations
“…The effect of drought on phloem-feeding insects has been variable. Drought has been reported to reduce the tness metrics such as survivorship, fecundity and density of phloem-feeding insects (Huberty et al 2004;Leybourne et al 2021), while other studies linked drought with an increase in pest abundance (Mattson et al 1987;Pretorius et al 2016). For example, moderate drought events have promoted populations of the rice root aphid (Rhopalosiphum ru abdominalis Sasaki), a pest of wheat (Triticum aestivum L.) (Kindler et al 2004).…”
Section: Introductionmentioning
confidence: 99%